2017
DOI: 10.12659/ajcr.905245
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Helical Tomotherapy and Direct Tomotherapy in Bilateral Whole Breast Irradiation in a Case of Bilateral Synchronous Grade 1 and Stage 1 Breast Cancer

Abstract: Patient: Female, 60Final Diagnosis: Complete remissionSymptoms: NoneMedication: —Clinical Procedure: RadiotherapySpecialty: OncologyObjective:Rare diseaseBackground:Synchronous bilateral breast cancer is rare. A case is presented where whole breast irradiation (WBI) was planned after breast conserving surgery in a patient with synchronous bilateral breast cancer. A comparison was made between the feasibility of helical tomotherapy and direct tomotherapy.Case Report:A 60-year-old woman was found to have bilater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Bilateral irradiation poses a particular treatment challenge, especially if internal mammary lymph nodes (IMN) are targeted, due to competing goals of target coverage and normal tissue sparing. There is relatively little published regarding treatment of these complex cases, mostly limited to case reports and dosimetric studies [4][5][6][7][8][9][10][11][12][13][14][15] . Proton beam therapy (PBT) is emerging as a promising treatment modality in patients with indications for regional nodal irradiation (RNI), especially in those with unfavorable anatomy, such as pectus excavatum or small lung volume, as PBT reduces dose to adjacent normal tissues including the heart and lungs [16][17][18][19][20] .…”
Section: Introductionmentioning
confidence: 99%
“…Bilateral irradiation poses a particular treatment challenge, especially if internal mammary lymph nodes (IMN) are targeted, due to competing goals of target coverage and normal tissue sparing. There is relatively little published regarding treatment of these complex cases, mostly limited to case reports and dosimetric studies [4][5][6][7][8][9][10][11][12][13][14][15] . Proton beam therapy (PBT) is emerging as a promising treatment modality in patients with indications for regional nodal irradiation (RNI), especially in those with unfavorable anatomy, such as pectus excavatum or small lung volume, as PBT reduces dose to adjacent normal tissues including the heart and lungs [16][17][18][19][20] .…”
Section: Introductionmentioning
confidence: 99%
“…They used 2.5-cm FW, 0.3 pitch, and 3.0 MF and concluded HT showed better homogeneous and conformal distribution and lesser mean dose to the OARs by specifically lowering the higher dose volumes. [ 9 ] These findings were supported by the study of Valentina Lancellotta, who compared HT plans with plan parameters such as FW: 5 cm, pitch: 0.287, and MF: 3 with TomoDirect[ 3 ] for bilateral synchronous Grade 1 and Stage 1 breast cancer and concluded HT was more suitable than direct tomotherapy. Studies reported the influence of planning parameters in helical planning for sites such as the prostate, head and neck, and breast, but the results depended on the dose/fraction, axial offset, and the beam blocking, etc.…”
Section: Discussionmentioning
confidence: 80%
“…Helical tomotherapy (HT) is capable to deliver well tolerated homogeneous dose to BBC without field overlapping. [ 2 3 ]…”
Section: Introductionmentioning
confidence: 99%
“…Several techniques based on IMRT, VMAT, and tomotherapy have been developed with reported equivocal benefits in cardiac sparing. [7][8][9][10][11] Based on the conventional VMAT model, we developed a novel two-stage optimization method, "Non-Uniform VMAT (NU-VMAT)," by removing unnecessary beams to reduce dose to OARs while maintaining sufficient dose coverage to targets. In this study, the performance of NU-VMAT was evaluated in comparison with conventional IMRT in terms of plan quality and delivery efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Currently, three-dimensional conformal radiation therapy (3D CRT), intensity-modulated radiation therapy (IMRT), volumetric modulated arc therapy (VMAT), and Tomotherarpy are commonly used in the treatment planning of breast cancer radiotherapy. [6][7][8][9][10][11][12][13][14] Comparative studies have shown that benefiting from the reverse optimization strategy IMRT and VMAT can achieve better dose distribution to the target and less dose exposure to the adjacent organs at risk than CRT. 12 Since the left breast is located in the vicinity of the heart, which makes the heart unavoidable to the radiation during the left breast radiotherapy.…”
Section: Introductionmentioning
confidence: 99%